2003
DOI: 10.1002/jmri.10393
|View full text |Cite
|
Sign up to set email alerts
|

Use of fast spin echo for phase shift magnetic resonance thermometry

Abstract: Purpose: To propose a modified fast spin echo (FSE) magnetic resonance imaging sequence for MR thermometry, employing the proton resonance frequency (PRF) shift by means of MR phase maps. Despite their obvious advantages of speed and high signal-to-noise ratio (SNR), FSE sequences have not until now been used for this purpose due to the restraints imposed by the Carr-Purcell-Meiboom-Gill (CPMG) conditions. Materials and Methods:The new FSE combines a new phase modulation scheme that maintains magnetization tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A potential solution to this problem is the incorporation of dual‐band irradiation pulses for the simultaneous excitation of the PCr and Pi peaks (49, 50). Phase images of Pi can be made very sensitive to even small changes in the chemical shift, which is the principle of MR thermometry in 1 H‐MRI (51, 52).…”
Section: Discussionmentioning
confidence: 99%
“…A potential solution to this problem is the incorporation of dual‐band irradiation pulses for the simultaneous excitation of the PCr and Pi peaks (49, 50). Phase images of Pi can be made very sensitive to even small changes in the chemical shift, which is the principle of MR thermometry in 1 H‐MRI (51, 52).…”
Section: Discussionmentioning
confidence: 99%
“…Vogel et al have reported on a modified fast spin echo sequence that enables PRF thermometry (41). This can have a particular benefit in generating high SNR images as lower field strengths, typically used for interventional imaging (0.2-0.5T).…”
Section: Proton Resonance Frequency (Prf) -Temperature Mappingmentioning
confidence: 98%
“…However, its application is quite difficult as the method requires precise adjustments of the receiver phase and the procedure for calculating the list of refocusing pulse flip angles and phases is quite complicated. This method has already been successfully applied to MR thermometry [13] in which a temperature map was obtained by mapping magnetization phase shifts caused by the precession frequency shifts induced by temperature changes in the sample.…”
Section: Introductionmentioning
confidence: 99%